1967
DOI: 10.1113/jphysiol.1967.sp008340
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary lymph flow and the uptake of liquid from the lungs of the lamb at the start of breathing

Abstract: 1. Lymph from the lungs of lambs and sheep was found to enter both the right lymph duct and the thoracic duct. Right lymph duct flow was collected by constructing a venous sac, the venous tributaries of which were ligated but which the right lymph duct entered; thoracic duct flow was collected by cannulating the duct. Lymph from sites other than the lungs was excluded from the collections.2. Measurements were made of the surface tension characteristics of lung extracts and of the liquid present in foetal lungs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
1

Year Published

1969
1969
1995
1995

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(69 citation statements)
references
References 24 publications
6
62
0
1
Order By: Relevance
“…Lung liquid was sampled via the tracheal cannula and blood was obtained from the carotid artery. In two experiments, samples of pulmonary lymph were obtained by cannulating the thoracic duct and 329 R. E. OLVER AND L. B. STRANG excluding non-pulmonary sources of lymph as described by Humphreys, Normand, Reynolds & Strang (1967).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung liquid was sampled via the tracheal cannula and blood was obtained from the carotid artery. In two experiments, samples of pulmonary lymph were obtained by cannulating the thoracic duct and 329 R. E. OLVER AND L. B. STRANG excluding non-pulmonary sources of lymph as described by Humphreys, Normand, Reynolds & Strang (1967).…”
Section: Methodsmentioning
confidence: 99%
“…It is difficult to aspirate more than half of that actually present through a tracheostomy, so it is unlikely that more is expelled through the mouth during vaginal delivery and even less is likely to be drained away after Caesarean section. From lung weight and lymph flow measurements, Humphreys et al (1967) showed that much of the liquid is cleared by lymphatics from the interstitial spaces of the lung over a period of 5-6 hr, but it seems likely that it must be displaced from the alveolar spaces much more rapidly, otherwise efficient gas exchange would not be possible. The experiments with cyanide show that when the secretion is stopped, absorption takes place at 5-18 ml./hr, presumably down the gradient of water activity which exists because of the difference in protein concentration between lung liquid and plasma, exerting an osmotic pressure of about 25 mmHg (see Boston, Humphreys, Normand, Reynolds & Strang (1968) for protein osmotic pressure values).…”
Section: R E Olver and L B Strang Secretion And Absorption Of Lunmentioning
confidence: 99%
“…16 The majority of pulmonary lymph drains to the right lymphatic duct 5 ' 16 '" with some pulmonary lymph draining to the thoracic duct. 12 This was confirmed in two additional baboons in which Evans blue dye was instilled into the trachea. Dye was noted to drain predominantly to the right lymphatics.…”
Section: Discussionmentioning
confidence: 60%
“…16 Division of the right cervical lymphatic chain and interruption of the right arm lymphatics eliminated these sources of contamination of pulmonary lymph. 12 The right lymph collected in this experiment probably contained some cardiac lymph 12 and thus cannot be considered pure pulmonary lymph. However, it was found to be strikingly different from thoracic duct lymph and thus seems to represent principally pulmonary lymph.…”
Section: Discussionmentioning
confidence: 99%
“…4 is part of a gradual trend that begins earlier in gestation and continues after birth until adult values are obtained. During late gestation, the increase in the plasma: interstitial volume ratio might be due to the increase in plasma colloid osmotic pressure with age (Lumbers et al 1991), which would tend to hold fluid in the vascular compartment, and the rise in lymphatic flow with age (Humphries, Normand, Reynolds & Strang, 1967), which would return escaped fluid to the vascular compartment. The effect of the rise in plasma colloid osmotic pressure may be magnified by a fall in capillary permeability to protein with age .…”
Section: Body Fluid Compartments Ecvmentioning
confidence: 99%